Association of ZFHX3 genetic polymorphisms and extra-pulmonary vein triggers in patients with atrial fibrillation who underwent catheter ablation. (19th May 2022) - Hwang, I; Kwon, O-S; Hong, M; Yang, S-Y; Park, J-W; Yu, H T; Kim, T-H; Uhm, J-S; Joung, B; Lee, M-H; Pak, H-N
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Health and Welfare, National Research Foundation of Korea (NRF) Abstract Background: The ZFHX3 gene (16q22) is the second most highly associated gene with atrial fibrillation (AF) and is related to inflammation and fibrosis. Purpose: We hypothesized that ZFHX3 is associated with extra-pulmonary vein (PV) triggers, left atrial (LA) structural remodeling, and poor rhythm outcomes of AF catheter ablation (AFCA). Methods: We included 1782 patients who underwent a de novo AFCA (73.5% male, 59.4±10.8 years old, 65.9% paroxysmal AF) and genome-wide association study and divided them into discovery (n=891) and replication cohorts (n=891). All included patients underwent isoproterenol provocation tests and LA voltage mapping. We analyzed the ZFHX3, extra-PV trigger-related factors, and rhythm outcomes. Results: Among 14 single-nucleotide polymorphisms (SNPs) of ZFHX3, rs13336412, rs61208973, rs2106259, rs12927436, and rs1858801 were associated with extra-PV triggers. In the overall patient group, extra-PV triggers were independently associated with the ZFHX3 polygenic risk score (PRS) (OR 1.65 [1.22-2.22], p=0.001, model 1) and a low LA voltage (OR 0.74 [0.56-0.97], p=0.029, model 2). During 49.9±40.3 months of follow-up, clinical recurrence of AF was significantly higher in patients with extra-PV triggers (Log-rank p<0.001, HR 1.89 [1.49-2.39], p<0.001, model 1), large LA dimensions (Log-rank p<0.001, HR 1.03 [1.01-1.05], p=0.002, model 2), and low LA voltages (Log-rank p<0.001, HR 0.73 [0.61-0.86], p<0.001, model 2) but not the ZFHX3 PRS (Log-rank p=0.819). Conclusions: The extra-PV triggers had significant associations with both ZFHX3 genetic polymorphisms and acquired LA remodeling. Although extra-PV triggers were an independent predictor of AF recurrence after AFCA, the studied AF risk SNPs intronic in ZFHX3 were not associated with AF recurrence.